Megacity Expansion, Recharge Deficit, Groundwater Depletion and City Sustainability in Ahmedabad - Salahuddin, Ghazal (National Geographical Journal of India, 2022)
Indian megacities have massive population concentration due to rapid population growth in the wake of unprecedented globalization and reinforced tendency of economic centralization. India has eight megacities namely, Mumbai, Delhi, Kolkata, Chennai, Bangalore, Hyderabad, Ahmedabad and Pune ranging in population from 5 million to over 20 million persons. These cities, together account for a huge urban population of nearly 100 million persons. Most of these cities sustain on the groundwater resources of their immediate environment. There is enormous water mining because the per-capita domestic water demand is highest in the megacities due to consumer oriented lifestyle and higher purchasing power of the people. In addition to it, the industrial-commercial water demand is also very high. On the other hand, the megacities have burgeoning built-up surfaces. The built-up surfaces induce run-off losses and prevent groundwater absorption and recharge. Consequently, the water discharge-recharge balance is heavily distorted. It leads to continuous groundwater depletion underneath and the immediate surroundings. Even more alarming would be the future scenario of diminishing water sustainability in the megacities of India. Further, most of these megacities are the capitals of their respective states. These are the prestigious cities of India. Acute water shortages would lead to social unrest and political instability in the developed states of India. The main objectives of this paper are to analyse the population growth and areal expansion of these cities to estimate the problems of water shortages and its consequences.